CIVIL – MILITARY RELATIONS IN THE MINISTRY OF DEFENCE, NAMIBIA - Hauanga, Edward (My University, 2011)
The research report aims to fill the knowledge gap on the relationship between civil and military components within the Namibian Ministry of Defence, which have continued to co-exist without any investigation conducted on its impact on governance and management. The purpose of the research was to investigate this relationship, known as Civil-Military Relations, and its impact thereof on the institutional development and its functionality. Interviews were carried out with Ministry of Defence officers and civilian employees. Data or perceptions were collected from a number of senior officers using set questionnaires. The findings indicate some successes in terms of the Civil-Military Relations (CMR) Model, especially where both components establish respect for each other, not only by constitutional or statutory mandate but also in terms of attitude. Some limitations of the Model emerged from the findings and these were addressed through literature. The findings indicate an unexpected degree of agreement between the two components, where they exhibited the need for further enhancement of the CMR Model within the Ministry of Defence. The study has further demonstrated the evolution of CMR, as it is often fraught with complications and setbacks motivated by socioeconomic and political factors. The classical theory of the formal separation of the military from mainstream governance, as explored by Huntington, has been interrogated. Some critics of its application argue that it fails to recognize some of the major players in the security sector who play a pivotal role in ensuring that the national security strategy addresses the real security needs on the ground. This is civil society as an institution, with ideas and interests. Schiff’s concordance theory seems to arrest this concern as it calls for partnership among the major stakeholders (that is, political society, civil society and the military) to set the agenda for institutional development. In conclusion, the study offers suggestions for various designs for the CMR Model and points to the importance of a participatory approach to governance
MM - P&DM
Keywords: Defence, Ministry of, Namibia; Civil-military relations